PENGETAHUAN PERAWAT TENTANG PROGRAM PERKESMAS DI PUSKESMAS YANG MENERAPKAN PERKESMAS DI SLEMAN - Warseno, Agus (Jurnal Media Ilmu Kesehatan, 2018)
Background: The basic health services to the community is one of the development efforts of community approach which is undertaken by the health centers, namely PHN (Public Health Nursing). PHN aims to increase community self-reliance to achieve an optimal degree. Nurses in Health Center requires competence to provides health services in PHN Objective: The study aims to know the knowledge of nurses in health centers that have PHN programme in Sleman. Methods: The research is quantitative descriptive study. The study population was nurses in the health center of Gamping I, Ngaglik I, and Ngemplak I Sleman, as many as 16 nurses. The study uses total sampling technique. Data were analyzed using univariate analysis techniques. Results: The results showed a majority of female respondents characteristics as much as 81.2%, the Education level of majority of respondents were Diploma of Nursing as much as 93.8%, The level of knowledge of nurses about the aspects of the basic concept of PHN in sufficient category with a percentage of 56.2%, The level of knowledge of nurses about aspects of PHN in sufficient category has percentage of 87.6%, the level of knowledge of nurses about the aspect of minimal competence and the role of nurses in health centers is mostly in sufficient category with a percentage of 50.0%, The level of knowledge of nurses about aspects of the reporting of PHN more with enough category with a percentage of 81.3%, the level of knowledge of nurses about PHN are equal for good category and sufficient category with a percentage of 50.0%. Conclusion: The level of nurse knowledge about PHN is the same between good and sufficient categories Keyword: Knowledge, Public Health Nursing, Nurse